Determination of Glyoxylic Acid in Organic Electrosynthesis Using the Differential Pulse Polarography - Jin1, Ling; Pang1, Chaoxia; Zhang1, Xinsheng; Niu2, Li; Yuan1, Weikang (Asian Journal of Chemistry, 2013)
The differential pulse polarographic behaviour of glyoxylic acid was investigated in 10 % KOH solution. Glyoxylic acid displays a well-defined cathodic reduction peak at -1.30 V (vs. Ag/AgCl). The current responses were linear with the concentration of glyoxylic acid ranging from 1.35 × 10-4 to 8.10 × 10-4 M. The selectivity towards glyoxylic acid was distinct in the presence of other ions, such as Ca2+, Cu2+, Ni2+, Fe2+, Cl–, SO42- and NO3–. Furthermore, the peak potential for the reduction of glyoxylic acid distinctly shifted negatively about 50 mV in the presence of tetrabutylammonium hydroxide. The peak distorted to some extent but no splitting was observed. The non-linear calibration dependencies may be approximated by the Langmuir-type equation in the presence of tetrabutylammonium hydroxide. It is necessary to use at least twice standard additions in analysis procedure. The present method was successfully applied for the fast, simple, sensitive determination of glyoxylic acid in electroreduction industrial process with and without the chemical activator.